SOCIAL PARTNERSHIP AS KEY FACTOR OF NATIONAL-PATRIOTIC EDUCATION - Petrochko, Zhanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The problem of social partnership in the national-patriotic education is not studied enough, the strengths and weaknesses of social professionals to work together on patriotism are not disclosed. The purpose of the article: to reveal the essence and organizational and pedagogical conditions of effective social partnership in national-patriotic education on the basis of identifying the readiness of social professionals to such a partnership. The essence of the readiness of social specialists for national-patriotic education on the basis of social partnership was clarified. Such readiness is characterized by the presence of appropriate ideas, knowledge, values, skills and abilities for partnership in national-patriotic education. The list of specialists-subjects of national-patriotic education is determined. The results of the ascertaining stage of the experiment of all-Ukrainian level on the topic ‘System of Training Social Sphere Specialists for National-Patriotic Education of Children and Youth based on Social Partnership’ are presented. The article presents the results of the survey of 2,309 social professionals and partners in the national-patriotic education of children and youth. The organizational and pedagogical conditions for establishing partnership in national-patriotic education are determined. Emphasis is placed on the need to develop and actively implement interactive training programs for social workers on social partnership. According to the survey results, the content of such training should include such issues as: initiative and choice of partners, dialogue with them to engage in national-patriotic education, concluding agreements on effective / mutually beneficial partnership, creation and implementation of partnership projects.